Drying shrinkage, mechanical and transport properties of sustainable mortar with both recycled aggregate and powder from concrete waste. (15th May 2022) - Wu, Huixia; Wang, Changqing; Ma, Zhiming
Abstract: Utilizing recycled fine aggregate (RFA) and recycled fine powder (RFP) both from concrete waste to prepare fully recycled mortar benefits the recycling of construction waste. This investigation focused on the performance and modification of recycled mortar with both RFA and RFP, and the properties were obtained by micro- and macromeasurements. The results show that RFA contains abundant hardened cement mortar and has water absorption higher than natural aggregate, and that substituting RFP for 30% cement results in the reduction of hydration products and an increase of pore structure. Incorporating RFA increases the drying shrinkage of newly-prepared mortar, while the appropriate addition of RFP made from mortar and concrete waste reduces the drying shrinkage. Utilizing RFA and RFP are both detrimental to the mechanical strength and permeability resistance, and the performance degeneration of sustainable mortar is significant when high-volume RFA and RFP are incorporated. A linear relationship exists between the total porosity and transport properties of sustainable mortar with RFA and RFP. Substituting active mineral admixtures for a portion of RFP benefits the properties of fully recycled mortar with RFA and RFP; specifically, the addition of 10% silica fume or 10% metakaolin increases the mechanical strength by 35.9% and 38.1% and leads to decreases of 31.4% and 48.4% in the capillary absorption coefficient of fully recycled mortar, respectively. In addition, it is also beneficial for the properties of such sustainable mortar to add a mixture of RFP and recycled clay brick powder, which are both derived from construction waste. Highlights: Giving a comparison on the performance of mortar with recycled aggregate and recycled powder. Utilizing both recycled aggregate and recycled powder to prepare fully recycled mortar. Properties and modification of the fully recycled mortar with recycled aggregate and powder.